2007
DOI: 10.1631/jzus.2007.b0162
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PCV2 DNA by SYBR Green I-based quantitative PCR

Abstract: Abstract:We developed an assay for the detection and quantitation of porcine circovirus type 2 (PCV2) with the SYBR Green I-based real-time PCR. The real-time PCR provides a broad dynamic range, detecting from 10 3 to 10 11 copies of DNA per reaction. No cross-reactions were found in specimens containing PCV1. Because of the high sensitivity and specificity of the assay with a relatively rapid and simple procedure, real-time PCR can be used as a routine assay for the clinical diagnosis of PCV2 infection. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
(32 reference statements)
4
29
0
1
Order By: Relevance
“…Detection over a wide dynamic range of concentrations by ddPCR allows for the measurement of viral ranges in animals, which can exhibit various levels of infection. 16 In the present study, the linear regression correlation coefficients were measured using either ddPCR or TaqMan real-time PCR showed good R 2 values that were ~1 (Fig. 2).…”
supporting
confidence: 60%
“…Detection over a wide dynamic range of concentrations by ddPCR allows for the measurement of viral ranges in animals, which can exhibit various levels of infection. 16 In the present study, the linear regression correlation coefficients were measured using either ddPCR or TaqMan real-time PCR showed good R 2 values that were ~1 (Fig. 2).…”
supporting
confidence: 60%
“…In contrary, Ct of NTC seems increase as lower annealing temperature was used (Figure 3ac). Presence of NTC was common, especially when non specific dye such as SYBR green I was used (Yang et al, 2007). Bustin et al, (2009) reported that NTC was negligible at distance of Ct sample was more than 5 because, in this distance, Ct of NTC and sample was distinguishable.…”
Section: Optimization Of Tm Shift Sybr Green I Qpcr Techniquementioning
confidence: 99%
“…We used PCR to detect Mycoplasma hyopneumoniae, Bordetella bronchiseptica, Pasteurella multocida, porcine circovirus 2 (PCV2), Suid herpesvirus 1 (SuHV-1), and porcine parvovirus (PPV) as described previously (Artiushin et al 1993;Register and DeJong 2006;McKillen et al 2007;Yang et al 2007;Tang et al 2009). The extracted DNA was also tested for b-actin as described by Hui et al (2004).…”
Section: Detection Of Nucleic Acids From Different Infectious Agentsmentioning
confidence: 99%